The Implications of Motor and Cognitive Inhibition for Hot and Cool Executive Functions: The Case of Quadrato Motor Training - Leshem, Rotem; De Fano, Antonio; Ben-Soussan, Tal Dotan (Frontiers in Psychology, 2020)
Enabling us to stop ongoing or prepotent responses and to control interference, motor inhibition facilitates the development of executive functions like thought before action, decision-making, and self-regulation of affect, motivation, and arousal. In the current paper, we characterize the relationship between motor inhibition and the executive functioning system, in the context of its proposed division into predominantly affective (hot) and predominantly cognitive (cool) components with corresponding neural trajectories originating in the prefrontal cortex. We then assert that this division is central to understanding the effects of structured movement practice on EF-based abilities including self-control and self-regulation. In this context, we review a structured sensorimotor training practice known as Quadrato Motor Training, and discuss its effects on crucial mechanisms of integration between the different EF components.